The Determinant Factors for the Adoption of IFRS in Africa - Schutte, Daniel; Omotoso, Matthew Olubayo; Oberholzer, Merwe (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
Many countries worldwide have converted local accounting standards to the International Financial Reporting Standards (IFRS). Although most countries embraced the IFRS, only a few African countries adopted global accounting standards in their current form. This paper extends the literature by investigating potential factors influencing the adoption of IFRS on the African continent and contributes significantly to the current knowledge in the field. The study employs a panel data logistic regression using the random‑effects statistical estimation technique to compare African countries that adopted the IFRS to non‑adopting countries from 2005 to 2019. The findings suggest that culture, external pressure, investor protection, market capitalisation, and trade openness are the predicted springboards determining African countries’ decisions to adopt the IFRS. These findings provide valuable insight for standard‑setters, enabling them to effectively promote the IFRS among African countries that have not adopted the IFRS in their current form.